Mayūrakāvyavivecana : Bhāgavatī kāvyañcyā tulanātmaka vistrta nirīkshaṇāsaha - Banahaṭṭī, Śrīnivāsa Nārāyaṇa, 1901- (SAMP early 20th-century Indian books project, 1926)
Study on the works of Moropanta, 1729-1794, Marathi poet; includes comparison of his works with other Marathi poems based on the Bhāgavatapurāṇa.